Trophic Diversification Out of Ancestral Specialization: An Example from a Radiating African Cyprinid Fish (Genus Garra) - Aleksandra S. Komarova; Alexander S. Golubtsov; Boris A. Levin (Diversity, 2022)
Trophic resource partitioning is one of the main ecological mechanisms of adaptive radiation. The Garra is a highly specialized periphyton feeder that has widened jaws equipped with a horny cutting scraper. In a river located in the Ethiopian Highlands in East Africa, a diversification of Garra composed of six sympatric ecomorphs which were strikingly diverse in trophic morphology was revealed. A hypothesis on trophic resource partitioning was tested using data on diet composition, gut length, and stable isotopes. The obtained results confirmed the trophic diversification of Garra ecomorphs. Three feeding modes were revealed: (i) periphytonophagy, (ii) mixed periphytonophagy and zoophagy, and (iii) zoophagy. The periphyton feeders had a long gut and were enriched in δ13C values compared to the shorter gut and lowered δ13C values in the zoophagous ecomorphs. Therefore, Garra could respecialize out of its ancestral specialization. This finding does not support the generalists-to-specialists hypothesis on the origin of specializations, and suggests that Liem’s paradox is a more common phenomenon. In the case of specialists, we assume that new ecological opportunities can be ‘visible’ to specialists if they are preceded by relaxed selection constrains that lead to the widening of the ecological/morphological plasticity to jump out of a canalized mode of ancestral specialization.